1986
DOI: 10.1113/jphysiol.1986.sp016090
|View full text |Cite
|
Sign up to set email alerts
|

Organization of motor units following cross‐reinnervation of antagonistic muscles in the cat hind limb.

Abstract: SUMMARY1. Peripheral reorganization of nerve and muscle properties was studied following misdirection of regenerating axons to foreign muscles. The tibial nerve, which innervates all of the distal extensor muscles, was cross-united with the common peroneal nerve, which innervates all of the distal flexor muscles, in one hind limb of seven 2-6 month old cats. After 18-24 months the properties of the motor units in the reinnervated triceps surae muscles were studied by dissection and stimulation of the ventral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Full recovery of motoneuron properties and synaptic contacts onto axotomised motoneurons occurs following muscle innervation.33 When motoneurons reinnervate their former or antagonistic muscles, the physiological relationships between nerve and muscle properties also retumed to normal. Th-us, the tension and contractile speed of the muscle units were directly related to the amplitude of the extracellularly recorded action potential, as found in normally innervated muscles.12 34 Self-reinnervated muscles function appropriately during locomotion. In comparison, cross-reinnervated cat muscles typically fired according to the pattern expected of the innervating motor pool during locomotion.35-3 Therefore, these data would tend to suggest that even though nerve and muscle unit properties are reestablished after nerve section and resuture, the motor units are recruited at a level of force that is appropriate within their original motor pool as is proposed here.…”
Section: Innervation Of Reinnervated Musclesmentioning
confidence: 88%
“…Full recovery of motoneuron properties and synaptic contacts onto axotomised motoneurons occurs following muscle innervation.33 When motoneurons reinnervate their former or antagonistic muscles, the physiological relationships between nerve and muscle properties also retumed to normal. Th-us, the tension and contractile speed of the muscle units were directly related to the amplitude of the extracellularly recorded action potential, as found in normally innervated muscles.12 34 Self-reinnervated muscles function appropriately during locomotion. In comparison, cross-reinnervated cat muscles typically fired according to the pattern expected of the innervating motor pool during locomotion.35-3 Therefore, these data would tend to suggest that even though nerve and muscle unit properties are reestablished after nerve section and resuture, the motor units are recruited at a level of force that is appropriate within their original motor pool as is proposed here.…”
Section: Innervation Of Reinnervated Musclesmentioning
confidence: 88%
“…Specificity of reinnervation in whole muscles may better be characterized by description of their motor unit population (Burke, Levine, Tsairis & Zajac, 1973;Kugelberg, 1973;Gordon & Stein, 1982a;Gordon, Stein & Thomas, 1986). At the single motor unit level, proportions of fast and slow motor unit types in reinnervated cat muscles after resuture of a single muscle nerve were normal (Gordon & Stein, 1982a).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the MG muscle and its innervation were surgically isolated for EMG and force recordings in response to stimulation of single axons or the MG nerve. Evoked action potentials of single MG motor nerves were recorded extracellularly using a triphasic electrode configuration in which EMG pickup was minimized (Gordon et al 1986). The distal tendon of the MG muscle was fastened to a force transducer for recording isometric whole muscle (Grass FT 10) and motor unit force (Kulite transducer).…”
Section: Methodsmentioning
confidence: 99%
“…Developmentally, the regulation of muscle fibre contractile and metabolic properties has generally been attributed to some property of the innervating motoneurone (Vrbova et al 1995). However, following axonal regeneration, several studies at the single motor unit level have indicated that neural conversion of reinnervated muscle fibres properties is incomplete (Dum, O'Donovan, Toop, Tsairis, Pinter & Burke, 1985; Gordon, Stein & Thomas, 1986; Foehring, Sypert & Munson, 1986 b ; Gillespie, Gordon & Murphy, 1987; Gordon, Thomas, Stein & Erdebil, 1988; Cope, Webb & Botterman, 1991; Unguez, Roy, Pierotti, Bodine‐Fowler & Edgerton, 1995). The factors limiting complete neural conversion of muscle fibre properties following regeneration in the adult are not known.…”
mentioning
confidence: 99%